Pharmacological characterization of liquiritigenin, a chiral flavonoid in licorice - Samaa Alrushaid; Neal M Davies; Stephanie E Martinez; Casey L Sayre (Wolters Kluwer Medknow Publications, 2016)
Liquiritigenin is a chiral flavonoid present in plant based food, nutraceuticals, and traditional medicines. It is also an important ingredient present in licorice. The purpose of this study is to explore the pharmacological activity of racemic liquiritigenin utilizing several in vitro assays with relevant roles in colon cancer and diabetes. Where possible, the pure enantiomers were tested to identify the stereospecific contribution to the activity. In vitro antioxidant, anticancer, anti-inflammatory activities (cyclooxygenase inhibition), antidiabetic activities (alpha-amylase and alpha-glucosidase inhibition) as well as cytochrome P450 (CYP450) inhibitory activities were assessed. Racemic liquiritigenin demonstrated a dose-dependent inhibition of alpha-amylase enzyme whereas its pure enantiomers did not. Racemic liquiritigenin showed moderate antiproliferative activity on a HT-29 (human colorectal adenocarcinoma) cancer cell line that was dose-dependent and potent inhibitory effects on the cyclooxygenase-2 enzyme. The flavonoid did not inhibit the activity of cytochrome CYP2D6 over the concentration range studied but was a potent antioxidant. The current study demonstrated the importance of understanding the stereospecific pharmacological effects of liquiritigenin enantiomers in alpha-amylase inhibition.